Enzymatic PCL-grafting to NH2-end grouped silica and development of microspheres for pH-stimulated release of a hydrophobic model drug - Kaptan, Yasemin; Güvenilir, Yüksel (Elsevier BV, 2022)
This study set out to evaluate novel PCL-based silica containing nanohybrids as the polymer matrix in a hydrophobic drug-loaded microsphere system. Nanohybrids were synthesized by PCL-grafting to NH2-end grouped silica by in situ enzymatic ring opening polymerization of ε-caprolactone. Molecular weight and monomer conversion, PCL grafting percentage, thermal properties and crystallinity of the nanohybrids were determined by 1H NMR, TGA, DSC and XRD. Synthesized nanohybrids had low crystallinity percentage (32 and 39 %) and molecular weight (4800 and 8700 g/mol), promising for controlled drug release applications. The nanohybrids were used for fabrication of trans-chalcone-loaded microspheres by O/W single emulsion solvent evaporation. Mean particle diameter of the microspheres were between 15 and 30 µm. The result of release studies showed that optimum microsphere formulations (AP4 and A2, respectively) had 61 and 64 % encapsulation efficiency. One of the more significant findings to emerge from this investigation is that TC release was extended to 16 and 37 days, in a controlled manner. TC release was significantly enhanced in acidic pH media (pH 3.6 and 5.6) indicating pH-dependent release from nanohybrid microspheres; releasing 80-100 % of the loaded drug in 4-14 days. Drug/polymer interactions and molecular structures were investigated by FT-IR spectroscopy and DSC analysis. According to the results obtained, enzymatically synthesized nanohybrids have potential for pH-dependent release of the model drug, trans-chalcone.
Keywords: Polymers; Spectroscopy, Fourier Transform Infrared; Hydrogen-Ion Concentration; Silicon Dioxide